A genetic screen for vascular mutants in zebrafish reveals dynamic roles for Vegf/Plcg1 signaling during artery development - Covassin, L.D.; Siekmann, A.F.; Kacergis, M.C.; Laver, E.; Moore, J.C.; Villefranc, J.A.; Weinstein, B.M.; Lawson, N.D. (Developmental biology, 2009)
In this work we describe a forward genetic approach to identify mutations that affect blood vessel development in the zebrafish. By applying a haploid screening strategy in a transgenic background that allows direct visualization of blood vessels, it was possible to identify several classes of mutant vascular phenotypes. Subsequent characterization of mutant lines revealed that defects in Vascular endothelial growth factor (Vegf) signaling specifically affected artery development. Comparison of phenotypes associated with different mutations within a functional zebrafish Vegf receptor-2 ortholog (referred to as kdr-like, kdrl) revealed surprisingly varied effects on vascular development. In parallel, we identified an allelic series of mutations in phospholipase c gamma 1 ( plcg1). Together with in vivo structure–function analysis, our results suggest a requirement for Plcg1 catalytic activity downstream of receptor tyrosine kinases. We further find that embryos lacking both maternal and zygotic plcg1 display more severe defects in artery differentiation but are otherwise similar to zygotic mutants. Finally, we demonstrate through mosaic analysis that plcg1 functions autonomously in endothelial cells. Together our genetic analyses suggest that Vegf/Plcg1 signaling acts at multiple time points and in different signaling contexts to mediate distinct aspects of artery development.